Editorial column as self-promotion for publishers - Mudra, Iryna (Lviv Polytechnic Publishing House, 2015)
Freedom of thought and style, which came to replace the prescriptive monoideological press, predominant communicative function of journalism, market conditions, freedom of thoughts expression, appearance of authorial journalism – these new tendencies of modern Ukrainian journalism cause the interest to the author of the Media whose point of view has the authority and interest on its own, and it resulted in appearance of new genre form – editorial column.
Keywords: Editorial column; marketing; promotion; journalism